2013
DOI: 10.1088/0965-0393/21/3/035007
|View full text |Cite
|
Sign up to set email alerts
|

Micro-plasticity and intermittent dislocation activity in a simplified micro-structural model

Abstract: Here we present a model to study the micro-plastic regime of a stress-strain curve. In this model an explicit dislocation population represents the mobile dislocation content and an internal shearstress field represents a mean-field description of the immobile dislocation content. The mobile dislocations are constrained to a simple dipolar mat geometry and modelled via a dislocation dynamics algorithm, whilst the shear-stress field is chosen to be a sinusoidal function of distance along the mat direction. The … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
32
0
4

Year Published

2013
2013
2019
2019

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 31 publications
(39 citation statements)
references
References 58 publications
3
32
0
4
Order By: Relevance
“…The model has been solved analytically in the mean-field theory (MFT) approximation, which assumes that the interactions have infinite range, i.e., they do not decay with distance [22,23]. MFT exactly predicts the scaling behavior of the slip statistics in three dimensions as described below, and agrees well with discrete dislocation-dynamics simulations [24][25][26] and experiments [27]. In the following, we compute the slip statistics for sufficiently slow driving in the quasistatic limit.…”
Section: Model Assumptions and Experimental Detailssupporting
confidence: 53%
“…The model has been solved analytically in the mean-field theory (MFT) approximation, which assumes that the interactions have infinite range, i.e., they do not decay with distance [22,23]. MFT exactly predicts the scaling behavior of the slip statistics in three dimensions as described below, and agrees well with discrete dislocation-dynamics simulations [24][25][26] and experiments [27]. In the following, we compute the slip statistics for sufficiently slow driving in the quasistatic limit.…”
Section: Model Assumptions and Experimental Detailssupporting
confidence: 53%
“…Currently there are two main variants of the universality class associated with the plastic deformation of crystalline materials, those for which the system is in a state of criticality irrespective of the applied external stress [46,58,59] and those for which the system is only in a state of criticality at (or close to) a critical depinning stress [60,61].…”
Section: Statistical Analysis Of Stress Dropsmentioning
confidence: 99%
“…On the other hand, other researchers (Dahmen et al, 2009;Derlet and Maaß, 2013;Friedman et al, 2012;Ng and Ngan, 2008c) pointed out that s 0 is not only related to sample size but also related to the current stress τ ( )…”
Section: The Cut-off Strain Smentioning
confidence: 99%
“…Self-organized criticality (SOC) model (Csikor et al, 2007;Zapperi et al, 1995) assumed that the cutoff size s max of the largest observed avalanche exclusively depends on the system size and not on the other experimental parameters. Meanwhile, mean-field theory (MFT) (Dahmen et al, 2009;Derlet and Maaß, 2013;Friedman et al, 2012;Ng and Ngan, 2008c) predicted that the cut-off size s max can also depend on stress. With two statistics gathered from experiments as input, Ng and Ngan (Ng and Ngan, 2008a) developed a Monte Carlo model to account for the jerky deformation during loading.…”
Section: Molecular Dynamics (Md) and Discrete Dislocation Dynamics (Dmentioning
confidence: 99%